Penerapan Metode Eksperimen dalam Meningkatkan Keterampilan Penggunaan Termometer pada Siswa Kelas V: Indonesia - Hana Azalia (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
Our research is oriented towards measuring the level of skill improvement of grade 5 students of SDIT Asy-Syafi'i Kabupaten Konawe in using laboratory thermometer measuring instruments in the subject of Natural Science (IPA) by applying the experimental method. The methodology applied is class action research (PTK), referring to the Arikunto (2008) model with 4 steps, namely planning/planning, action implementation, observation, and evaluation. The research was carried out in two cycles on the theme of heat with research subjects totaling 7 students. The tools used were monitoring sheets of students' skills in using laboratory thermometers. The results showed that the application of the experimental method succeeded in improving students' skills. In cycle 1, there was an increase in the average skill score of 25.70% after applying the experimental method, from the average pre-test score of 58.57 to 73.57 in the post-test. In cycle 2, although the percentage increase was lower at 11.80%, it still showed an increase in the average score from 78.57 in the pre-test to 87.86 in the post-test. The success of the experimental method is due to the direct involvement of students in the process of observation and measurement, as well as the development of observation skills, analysis, data accumulation, and conclusion making. Factors such as the level of difficulty of the material, motivation, concentration, learning environment, and students' physical condition can affect the percentage of skill improvement in each cycle.